Agricultural and economic development strategies and the transformation of China and India - von Braun, Joachim; Gulati, Ashok; Fan, Shenggen (International Food Policy Research Institute, 2005)
The reform experiences of China and India—similar in some ways and different in others—shed light on the enormous potential for investments and policies in support of pro-poor agricultural and rural growth to fight poverty and malnutrition in developing countries.